A thin line between Meniere’s disease and spontaneous intracranial hypotension syndrome - Iva Botica; Anđelko Vrca; Martina Špero; Marin Šubarić; Tomislav Carić; Marija Vrca Botica; Jelena Kovačić; Kristijan Makaruha; Aleksandra Roglić (Medicinski glasnik, 2016)
Aim: To point out the similarity of Meniere disease and spontaneous intracranial hypotension and difference of their treatment. Methods: A case of a 54-year-old male patient with previously diagnosed Meniere’s disease and newly diagnosed spontaneous intracranial hypotension syndrome is presented. Additional neuroradiological examination, Brain contrast-enhanced MRI and MR myelography were used for diagnosis. Results: Due to deterioration of vertigo, hearing loss and tinnitus in the right ear the patient was referred to the additional neuroradiological examination which confirmed the diagnosis of spontaneous intracranial hypotension syndrome. Brain contrast-enhanced MRI showed increased pachymeningeal contrast enhancement, and MR myelography identified the location of CSF leak. The patient was successfully treated conservatively. Conclusion: According to our knowledge this is the fifth case report of Meniere’s disease and spontaneous intracranial hypotension coexistence. Both diseases have similar clinical presentation and initial treatment. We suggest procedures of additional examination when the treatment fails and initial diagnosis becomes questionable.
Keywords: otogenic vertigo; intracranial hypotension; cerebrospinal fluid leakage